2019
DOI: 10.1021/acsaem.8b02148
|View full text |Cite
|
Sign up to set email alerts
|

High Thermoelectric Performance in Mg2(Si0.3Sn0.7) by Enhanced Phonon Scattering

Abstract: Owing to the high thermoelectric (TE) conversion efficiency, low cost, and environmental friendliness Mg 2 Si 0.3 Sn 0.7 solid solution has emerged as the material of choice for the n-leg of a TE generator for midtemperature (room temperature to 800 K) applications. Dimensionless TE figure-of-merit (ZT) values of 1.3 (at 700 K) have been reported in this compound when optimally doped. High ZT values in this compound are due to a combination of improved electrical properties (band convergence effect) and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 51 publications
1
34
1
Order By: Relevance
“…Mg 1.98 Cr 0.02 (Si 0.3 Sn 0.7 ) 0.98 Bi 0.02 recorded a maximum ZT value of 1.82 at 673 K, which is higher than any metal silicide thermoelectric material currently being produced. It also recorded an efficiency of 19.36% at 673 K. These results are in line with those of Goyal et al (2019), who doped Mg 2 Si 0.3 Sn 0.7 with bismuth (Bi) and chromium (Cr). Goyal et al found that the Bi increased the electrical conductivity due to band convergence, and introducing Cr caused embedded Cr and Sn nanoprecipitates to form within the material, helping to keep the thermal conductivity as low as possible [44].…”
Section: Enhanced Mid-temperature Thermoelectric Materialssupporting
confidence: 89%
See 1 more Smart Citation
“…Mg 1.98 Cr 0.02 (Si 0.3 Sn 0.7 ) 0.98 Bi 0.02 recorded a maximum ZT value of 1.82 at 673 K, which is higher than any metal silicide thermoelectric material currently being produced. It also recorded an efficiency of 19.36% at 673 K. These results are in line with those of Goyal et al (2019), who doped Mg 2 Si 0.3 Sn 0.7 with bismuth (Bi) and chromium (Cr). Goyal et al found that the Bi increased the electrical conductivity due to band convergence, and introducing Cr caused embedded Cr and Sn nanoprecipitates to form within the material, helping to keep the thermal conductivity as low as possible [44].…”
Section: Enhanced Mid-temperature Thermoelectric Materialssupporting
confidence: 89%
“…The reason for this drop in ZT is that in all four materials the thermal conductivity starts to increase rapidly from 500 K. This is because at 500 K MgAgSb starts transitioning away from the tetragonal α-MgAgSb into its intermediate tetragonal phase, β-MgAgSb. Then, at 650 K, it transitions into γ-MgAgSb, which has a cubic structure and is a poor thermoelectric material [43]. One reason for this is that it causes a large drop in carrier concentration and therefore electrical conductivity.…”
Section: Enhanced Mid-temperature Thermoelectric Materialsmentioning
confidence: 99%
“…The best results are obtained using multiple substitutions on both the magnesium and the silicon sites. These have led to materials with zT often exceeding 1.3 at 700 K with a record high zT of 1.7 for Mg 1.98 Cr 0.02 (Si 0.3 Sn 0.7 ) 0.98 Bi 0.02 at 680 K [788], although the stability, at the operating temperature, of the silico-stannides still being under investigation.…”
Section: Silicide Thermoelectricsmentioning
confidence: 99%
“…Figure 13. The maximum thermoelectric figure of merit, zT, of selected n-type magnesium silicides: Mg2Si0.97Bi0.03 [806], Mg2Si0.5875Sn0.4Sb0.0125 [807], Mg1.995La0.005Si0.58Sn0.42 [808], Mg2.10Si0.38Sn0.6Sb0.02 [809], Mg2Si0.487Sn0.5Sb0.013 [810], Mg2(Si0.3Sn0.7)0.975Sb0.025 [811], Mg2Si0.6Ge0.4B i0.02 [812], Mg2Si0.385Sn0.6Sb0.015 [813], Mg2Si0.3925Sn0.6Sb0.0075 [814], Mg2(Si0.4Sn0.6)0.97Bi0.03 [815], Mg2Si0.57Sn0.4Bi0.03 [816], Mg2.2Si0.49Sn0.5Sb0.01 [817], (Mg2.06Si0.3Sn0.68Bi0.02 [818], Mg2Si0.35Sn0.62Bi0.03 [819], Mg2(Si0.4Sn0.6)0.82Sb0.18 [820], Mg2Si0.53Sn0.4Ge0.05Bi0.02 [821], Mg2.08Si0.364Sn0.6Sb0.036 [789], Mg2.08Si0.37Sn0.6Bi0.03 [822], Mg1.98Cr0.02(Si0.3Sn0.7)0.98Bi0.02 [788]. Material Material Material Material Material 3.12.…”
Section: Silicide Thermoelectricsmentioning
confidence: 99%
“…Many studies denote that the doped Cr could promote the formation of nanoprecipitates, resulting in the reduction of the lattice thermal conductivity (κ L ) [12,13]. The Co-doped Cr and Bi could result in a ∼15% reduction in the lattice thermal conductivity (κ L ) compared to the only Bi doped sample while retaining similar PF values [13]. Along these lines, in this work, Cr/Sb is co-doped into Mg 2 Si 0.3 Sn 0.7 .…”
Section: Introductionmentioning
confidence: 99%